ANALYSIS OF THE ACCELERATION TIME AND OPTIMAL COSTS OF THE SHIPBUILDING PROJECT SPECIFIED IN THE ELECTRICAL SYSTEM WITH THE CRITICAL PATH METHOD - Agung Tresnadi; Suparno Suparno; Sutrisno Sutrisno (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT PT PAL Indonesia (Persero) is one of the strategic defense industries that produces Main Weapon Systems (Alutista) especially for the Indonesian Navy, and has a strategic role in supporting the development of the national marine industry. One of the benchmarks for the success of a new shipbuilding project is the length of time to complete both the stages of the production process and the entire project in addition to cost and quality of work. Therefore, research was conducted to optimize the planning of the production process time for a new shipbuilding project by creating a project network, looking for critical activities, and calculating the project duration. The method used to analyze costs and time is the critical path method, by accelerating the duration of activities that are on the critical path, then calculating changes in project costs that occur due to acceleration. The research objective with this critical path method is to determine the time and cost of the project and what activities are included in critical activities. In addition, it is also to control and coordinate various activities so that the project can meet the right timeframe and can also help companies plan and control projects in a more efficient time and cost. From the results of the analysis of project calculations during the initial conditions with normal working days without using overtime the company spent Rp. 1,963,108,000. Critical activities in initial conditions with 870 days for completion time conditions are accelerated by 710 days (total acceleration 160 days) with 16 critical trajectories covering 34 work activities where all activities enter critical trajectories. The difference between the initial working conditions and the accelerated conditions was 160 days. The new ship building project in the electrical system can be accelerated for 160 days at an additional cost of Rp. 3,525,214,127. Keywords: Shipbuilding project, Critical Path Method, Acceleration of time, and costs.